Ansiedade induzida pelo modelo de empatia para dor : o papel da neurotransmissão GABAa-benzodiazepínica na modulação da ansiedade em camundongos - Carmona, Isabela Miranda (Universidade Federal de São Carlos, 2017)
Anxiety is a fundamental emotional phenomenon, essential within the affective repertoire and its importance for the understanding of the emotional behaviors of the individuals promoted the development of preclinical studies that contribute to the understanding of the neurobilogical bases involved in this modulation. Studies have demonstrated the involvement of the amygdaloid complex in emotional behaviors related to anxiety and that and GABAA-benzodiazepine receptors play important role in the modulation of anxiety and nociception in animal models. Cohabiting with chronic pain produces an increase in anxiety in the observer mouse, these evidences support that through anxiety-like responses it is possible to observe the existence of emotional behavior present among the animals, characterized as empathy-like behaviors. This study investigated the effects of systemic and intra-amygdala injection of midazolam (MDZ), a GABAA-benzodiazepine receptor agonist, on the modulation of anxiety induced by cohabiting with a cagemate in neuropathic pain in mice exposed to the elevated plus-maze (EPM). For this, male Swiss mice were housed in pairs and after 14 days were divided into two groups: cagemate nerve constriction (CNC), in which one animal from each pair was subjected to sciatic nerve constriction; cagemate sham (Sham), one animal from each pair was subjected to the same surgery but without constriction and in the 28th day, the observer cagemates were submitted to EPM for five minutes. Experiment 1: the observer cagemates received systemic injections of saline or midazolam (0.5, 1.0 or 2.0 mg/kg, intraperitoneal, i.p.) and 30 minutes after were exposed to elevated plus-maze. Experiment 2: In the 23th day, bilateral cannulae were surgically implanted in the amygdala of the observer cagemate and in the 28th day, the observer cagemate received intra-amygdala injections of saline or midazolam (3 e 30 nmol/0,1µl) and 5 minutes after were exposed EPM. Two-way ANOVA followed by post hoc Duncan test revealed that living with a cagemate in neuropathic pain is able to increase anxiety-like behavior in mice, suggesting the influence that cohabiting with nociception causes in the observer cagemate. In the experiment 1, MDZ (1,0 e 2,0 mg/Kg) was able to produces anxiolytic-like effect on the EPM, characterized by increase the open arms exploration and decrease risk assessment-like behaviors, with the absence of significant changes in locomotor activity. In the experiment 2, in the same way MDZ was able to produces anxiolytic-like effect on the EPM. These results suggests that the cohabitation with a CNC induce anxiogenic-like responses in the observer mouse and the GABAA/benzodiazepine receptor complex located within the amygdala participates in modulation of anxiety-induced model of empathy in mice.
Anxiogenic-like behaviors by living with a conspecific in neuropathic pain condition are attenuated by injection of midazolam in mice
Keywords: Ansiedade; Empatia; Midazolam; Camundongos; Anxiety; Empathy; Mice; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::NEUROLOGIA, ELETROFISIOLOGIA E COMPORTAMENTO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::PSICOBIOLOGIA